Parametric Study on Dynamic Characterization of Homogeneous and Stratified Soil-Ash Deposit under Low-Strain and High-Strain Condition - Ram, Amit Kumar (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Parametric Study on Dynamic; Characterization of Homogeneous; and Stratified Soil-Ash Deposit; under Low-Strain; and High-Strain Conditions